Dynamics of International Standard Schools in Indonesia: Between Improving Quality and Access Inequality - Fiksi Juita; Fajri Ismail; Indah Wigati; Yuniar (Universitas Muhammadiyah Enrekang, 2026)
This article critically examines the policy dynamics and implementation of International Standard Schools (SBI) and their subsequent transformation into Partnership Education Units (SPK) in Indonesia, with a specific focus on the tension between educational quality enhancement and access inequality. Employing a qualitative research design, this study utilizes comprehensive policy document analysis alongside a systematic literature review of peer-reviewed academic publications from 2020 to 2026. The findings reveal that integrating international curricula, advancing pedagogical teacher competencies, and adopting English as a medium of instruction significantly improve instructional quality and students’ global readiness. Conversely, the implementation faces substantial criticism due to prohibitively high operational costs, urban-centric institutional distribution, and selective admission mechanisms, which collectively risk exacerbating socioeconomic stratification within the national education system. The analysis indicates that the regulatory transition from SBI to SPK reflects a deliberate governmental recalibration aimed at balancing global educational benchmarks with constitutional mandates for equity. This study concludes that optimizing international standard education necessitates inclusive policy interventions, including means-tested financial assistance, targeted infrastructure and teacher development in underserved regions, and rigorous financial transparency mechanisms. Ultimately, implementing these strategic measures can position international standards as effective catalysts for a more inclusive, high-quality, and sustainable national education transformation.